Vaspin Mediates the Intraorgan Crosstalk Between Heart and Adipose Tissue in Lipoatrophic Mice - Zhang, Donghui; Zhu, Hong; Zhan, Enbo; Wang, Fan; Liu, Yue; Xu, Wei; Liu, Xian; Liu, Jingjin; Li, Shufeng; Pan, Yong; Wang, Yongshun; Cao, Wei (Frontiers in Cell and Developmental Biology, 2021)
Lipoatrophy is characterized as selective loss of adipose tissues, leading the severity of cardiovascular disorders. Therefore, it is necessary to fully disclose the intraorgan crosstalk adipose tissue and cardiovascular in lipoatrophy. A-ZIP/F-1 mouse, a well-established lipoatrophic model, and primary cardiomyocytes was used for investigating the pathophysiological changes and molecular mechanisms. A-ZIP/F-1 mice had severe fat loss and impaired ventricular function, which was closely associated with reduction of vaspin. Administration of recombinant vaspin protein improved cardiac structural disorders, left ventricular dysfunction and inflammatory response. Vaspin also suppressed cardiac lipid deposits and enhanced mitochondrial biogenesis and activities. Interestingly, A-ZIP/F-1 mice transplanted with adipose tissues exhibited improvement of cardiac structural remodeling and mitochondrial function. Mechanistically, vaspin increased cardiac expression of phosphorylated AKT, which guaranteed the mitochondrial benefits of vaspin in primary mouse cardiomyocytes. The present study suggested that vaspin possessed biological benefits in attenuating lipoatrophy-induced cardiomyopathy onset, and targeting vaspin/AKT signaling was a potential strategy to maintain heart metabolism.